Faktor Sosial Ekonomi yang Mempengaruhi Petani dalam Penerapan Pengendalian Hama Terpadu (PHT) - Sunarru Samsi Hariadi (Jurnal Perlindungan Tanaman Indonesia, 1996)
For spreading concept of Integrated Pest Management (PHT), Agricultural Disease and Plant Controllers (PHP) and Field Agricultural Extension Workers (PPL) worked together for agricultural extension about integrated pest management through Field School of Integrated Pest Management (SLPHT), in the hope that farmers could adopt PHT in their rice field. The result of the research in Central Java and Yogyakarta Special Region Province showed that social economic factors namely farmers income, farmers knowledge about PHT, farmers attitude about PHT, and farmers participation in SLPHT influenced adoption of PHT.